THE RELATIONSHIP BETWEEN STRESS LEVEL, PICKY EATING BEHAVIOR, AND PHYSICAL ACTIVITY ON BODY MASS INDEX AMONG ADOLESCENT GIRLS - Fitriani, Dyah Ayu; Rofiasari, Linda; Yati, Asri Fitri; Ariani, Antri (Universitas Kusuma Husada Surakarta, 2025)
Background: Adolescence is a critical developmental period marked by significant physical, psychological, and social changes. An imbalance between energy intake and expenditure during this stage can lead to nutritional disorders, including underweight and overweight conditions. This study aimed to analyze the relationship between stress levels, picky eating behavior, and physical activity with Body Mass Index (BMI) among adolescent girls in Bandung Regency. Methods: This quantitative study employed a cross-sectional design involving 106 randomly selected high school female students. Data were collected using standardized questionnaires to assess stress levels (DASS-42), picky eating behavior (modified CEBQ), and physical activity (PAQ-A), along with direct anthropometric measurements to calculate BMI. Multivariate logistic regression analysis was used. Results: Stress level (p = 0.012; OR = 3.13), picky eating behavior (p = 0.003; OR = 5.42), and physical activity (p = 0.018; OR = 0.29) were significantly associated with BMI status. The findings highlight that a combination of stress, eating behavior, and physical activity plays a crucial role in influencing the nutritional status of adolescent girls. Conclusion: A comprehensive approach involving education, nutritional counseling, and promotion of active lifestyles is highly recommended within the school environment. Keywords: Adolescents, Body Mass Index, Physical activity, Picky Eating, Stress level